Joint effects of carotid plaques and renal impairment on the risk of cardiovascular disease and all-cause death in a community-based population: The Kailuan cohort study - Li, Wen; Bai, Wenkun; Miao, Congliang; Chen, Shuohua; Zhang, Xinyu; Fan, Yanfeng; Li, Xiao; Wu, Shouling; Liu, Xuemei; Hong, Jiang (Frontiers in Cardiovascular Medicine, 2022)
Objective Atherosclerosis contributes to the risk of cardiovascular disease (CVD) and all-cause death, but it is unknown whether atherosclerosis and renal impairment can further increase the risk of CVD and death. This study investigated the effects of carotid plaques and renal impairment on CVD and all-cause death in community-based populations. Method The study cohort consisted of 20,416 participants from Kailuan Study who complete carotid plaque ultrasound in 2012.Renal impairment was measured using the estimated glomerular filtration rate (eGFR) and proteinuria, as well as carotid plaque, jointed effects on CVD and all-cause death. Result Participants with the carotid plaque and eGFR<60ml/min & proteinuria had a 2.88-fold higher risk of all-cause death (95%CI, 2.18-3.80), which was significantly higher than those with alone factors (HR, 1.57; 95%CI, 1.04-2.36; and HR, 1.91; 95%CI, 1.56-2.32), compared to participants with no carotid plaque and eGFR≥60ml/min & proteinuria group. Participants with the carotid plaque and eGFR<60ml/min & proteinuria had a 1.05-fold higher risk of CVD (95%CI, 0.82-1.35), which was not higher than those with alone factors (HR, 1.35; 95%CI, 1.02-1.80; and HR, 1.12; 95%CI, 0.96-1.30), compared to participants with no carotid plaque and eGFR≥60ml/min & proteinuria group. Stratified analysis by age, participants with the carotid plaque and eGFR<60ml/min & proteinuria had a 2.98-fold higher risk of all-cause death (95%CI: 2.24-3.96), which was significantly higher than participants with alone factors (HR, 1.68; 95% CI, 1.10-2.59; and HR, 1.95; 95% CI, 1.59-2.40), compared to participants with no carotid plaque and eGFR≥60ml/min & proteinuria group in the age of ≥50 years. Participants with the carotid plaque and eGFR<60ml/min & proteinuria had a 1.66-fold higher risk of CVD (95%CI: 1.29-2.25), which was significantly higher than participants with alone factors (HR, 1.63; 95% CI, 1.20-2.22, and HR, 1.28; 95% CI, 1.11-1.49), compared to participants with no carotid plaque and eGFR≥60ml/min & proteinuria group, in the age of ≥50 years. Conclusion The joint of carotid plaques and renal impairment may further increase the risk of CVD and all-cause death compared with participants with alone factors in the age of ≥50 years, but not in the age of <50 years, from community-based study.